The wooden sculptures from Mephitis' sanctuary (Southern Italy). A dendrotypological approach for the analysis of woodworking technologies. (August 2021) - Capano, M.; Pignatelli, O.; Martinelli, N.; Gigli, S.; Terrasi, F.
Highlights: Wooden sculptures from the sanctuary of goddess Mephitis have been studied. Woodworking technology of Samnites is analyzed using dendrotypology. A non-uniform woodworking practice have been highlighted. The presence of several craftsmen or woodshops is supposed. Abstract: Several wooden objects discovered in the sanctuary of the goddess Mephitis in the Ansanto Valley (Southern Italy), and dated to the second half of the 1st millennium BC, are analyzed in this study with the aim of investigating the woodworking technologies of the ancient population, the Samnites, who venerated the goddess. No woodworking tools have been discovered during archaeological excavations and original tool-marks on the objects were covered during the restoration of the objects in the mid 20th century. Therefore, a dendrotypological approach was used to study the objects, though challenges to the analyses and interpretation of results arose from the non-optimal state of preservation of the wood and the materials used during restoration, which interrupt the tree-ring sequences. The analyzed features (wood taxon, tree age and size and part of the trunk isolated for the carving process) highlight the presence of non-uniform woodworking practices, which could be related to the presence of several craftsmen or woodshops, as attested in the ancient Greek world. The stylistic differences identified in the sculptures from the Ansanto Valley might refer to the social status of Samnite families who commissioned the ex-voto .